Hubungan Kualitas dan Harga dengan Keputusan Pembelian Smarthphone Samsung (Studi pada Mahasiswa Fakultas Ekonomi Universitas Buana Perjuangan Karawang) - Moh Fachrizal Nurhanansyah; Hartelina Hartelina; Banuara Nadeak (Universitas Batanghari, 2022)
This study aims to determine the relationship of product quality and price with the purchase decision of Samsung smartphones. This research was conducted on students of the Faculty of Economics, University of Buana Perjuangan Karawang as many as 100 respondents. The sample was selected using a non-probability sampling method with a purposive sampling technique. The type of research used in this research is descriptive exploratory with quantitative statistical research techniques. Data collection techniques in this study were through questionnaires, online media, books, journals and previous research. Data were tested using SPSS version 24.0 using validity test, reliability test, descriptive analysis, multiple correlation analysis and coefficient of determination analysis. The results reveal the fact that the product quality variable has a very strong positive relationship with purchasing decisions with a value of tx1y = 13.73 > ttable = 1.29025, the price variable has a very strong positive relationship with purchasing decisions with a value of tx1y = 12.05 > ttable = 1.29025, and the product quality and price variables have a very strong positive relationship with purchasing decisions with a value of tx1y = 39.89 > ttable = 1. The lower the product quality, the lower the Samsung smartphone purchase decision. The higher the price, the lower the decision to buy a Samsung smartphone.